“Beauty that reflects who we are”: femvertising in Avon campaigns - Frota, Natália Gomes; Barroso, Elane dos Santos Silva; Silva, Laíse do Nascimento; Mesquita, Rafael Fernandes de; Meneses, Rafael Martins de (Revista de Administração da UFSM, 2025)
Purpose: The objective of this study is to investigate consumers’ perceptions of femvertising campaigns. Specifically, the study examined whether consumers perceive themselves as represented by campaigns and the positive and negative effects of these representations. Design/Methodology/Approach: The article is characterized as a qualitative research study of a descriptive nature, utilizing focus groups with an average of eight participants per meeting. To process the data, content analysis was conducted, with the categories of analysis including the profile of participants, women in advertising, female representation, femvertising, and the impact of femvertising on the relationship with the brand. Findings: Consumers stated that Avon uses a wide variety of female representations in its advertising campaigns, showcasing people with characteristics that are considered relatable, with which they can identify. These characteristics were cited as brand differentiators. Originality: This article contributes to helping companies understand women’s perceptions of advertising campaigns with feminist messages, as well as understanding consumer behavior and what positioning they want from brands.